PELATIHAN KEMAMPUAN USAHA MIKRO KECIL MENENGAH MELALUI DIGITALISASI SEBAGAI STRATEGI BISNIS - nurhalim, andres dharma (Publika Citra Media, 2025)
The rapid development of digital technology has transformed business practices, including micro-enterprises. This community service activity aims to enhance the digitalization of micro, small, and medium-sized enterprises (MSMEs) in the Imam Bonjol area of Karawaci, involving businesses in the culinary, fashion, and various other sectors. The activity was conducted in three stages: interactive lectures, group discussions, and hands-on practice using digital platforms such as social media. The training materials covered the use of social media for marketing, digital content strategies, technology-based business management, and online transaction security. The expected targets of this activity are: 1) the community will gain knowledge and skills in utilizing Marketplace applications that facilitate online sales; 2) increased productivity of MSMEs; 3) increased efficiency and effectiveness of marketing, shifting from conventional methods to technology-based sales. The results of the community service program demonstrated a significant increase in participants' understanding and skills regarding digital technology, as well as successful implementation of digital marketing strategies and increased sales.